Activities of human exonuclease 1 that promote cleavage of transcribed immunoglobulin switch regions - Vallur, Aarthy C. (National Academy of Sciences, 2008)
Eukaryotic exonuclease 1 functions in replication, recombination, mismatch repair, telomere maintenance, immunoglobulin (Ig) gene class switch recombination, and somatic hypermutation. The enzyme has 5′–3′ exonuclease, flap endonuclease, and weak RNaseH activity in vitro, but it has been difficult to reconcile these activities with its diverse biological functions. We report robust cleavage by human exonuclease 1 of transcribed G-rich DNA sequences with potential to form G loops and G4 DNA. Predicted Ig switch recombination intermediates are substrates for both exonucleolytic and 5′ flap endonucleolytic cleavage. Excision is nick-dependent and structure-dependent. These results lead to a model for exonuclease 1 function in class switch recombination in which cleavage at activation-induced deaminase (AID)-initiated nicks produces gaps that become substrates for further attack by AID and subsequent repair.